Therapeutic Outcome of High Flow Nasal Cannula (HFNC) for Severe COVID-19 Patients in Isolation Intensive Care Unit - Baginda Aflah; Erwin Pradian; Nurita Dian Kestriani (Majalah Kedokteran Bandung, 2023)
This retrospective descriptive study aimed to understand the outcomes of HFNC therapy in severe COVID-19 patients admitted to isolation ICU during the period of January to June 2021 in Dr. Hasan Sadikin General Hospital Bandung, Indonesia. A total of 134 patients with severe COVID-19 were admitted to the isolation ICU and received HFNC. Among them, 44 patients (32.8%, N:134) were successfully weaned from HFNC and 90 patients (67.2%, N:134) failing HFNC with 10 patients (7.5%, N:134) died on HFNC use, 72 patients (53.9%, N:134) died on ventilator use, 4 patients (2.9%, N:134) moved rooms under HFNC use, and 4 patients (2.9%, N:134) moved to non-ICU isolation with ventilator use as the outcome. Patients’ median age was 60 years, most were male (52.3 %, N:134), median BMI was 25.4 kg/m2, with hypertension and diabetes mellitus as the main comorbidities. There was an improvement in the SpO2 on the first day after the use of HFNC. The ROX index had a median value of 3.6 on the first day, with the lowest ROX index of 3.2 and the highest of 4.4 during the treatment time. There was an improvement in the P/F Ratio in successful patients with a median initial P/F Ratio of 86.7 to 200.1 at the end of treatment. Overall, HFNC improves the hypoxemic conditions in early admission but does not correlate with general patient outcomes.